Digital Public Relations Strategy for Promoting E-Filing Services to Enhance Public Service at the Pratama Tulungagung Tax Office - Robby Wahyudi; Ulfi Nurfaiza; Fikri Amiruddin Imsani (Feedback International Journal of Communication, 2024)
The Pratama Tulungagung Tax Service Office is embracing the rapid advancements in technology, which necessitates the use of digital media to enhance its operations, particularly in public service delivery. This study aims to investigate the digital public relations (PR) strategies employed to promote E-Filing services and improve public service quality at the Pratama Tulungagung Tax Service Office. Specifically, the research examines how digital PR leverages social media platforms, such as Instagram, Facebook, Twitter, and YouTube, to communicate effectively with the public. By utilizing these platforms, the office aims to raise awareness and improve the accessibility of its E-Filing services, ultimately enhancing user experience and satisfaction. This research employs a qualitative methodology, with data gathered through a combination of observations, interviews, and documentation at the Pratama Tulungagung Tax Service Office. Data analysis focuses on the strategic use of digital media by the office's PR team to reach and engage a wider audience, thereby improving the public's understanding and use of E-Filing services. The findings that digital PR plays a significant role in facilitating the dissemination of information related to E-Filing services, contributing to more efficient and transparent public service delivery. The study concludes that effective digital communication strategies not only promote service awareness but also enhance the overall quality of public services provided by the Pratama Tulungagung Tax Service Office.